2013
DOI: 10.2147/ijwh.s49909
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cohort study of the effects of obesity in early pregnancy on maternal weight gain and obstetric outcomes in an obstetric population in Africa

Abstract: ObjectiveThe purpose of this study was to compare maternal weight gain in pregnancy and obstetric outcomes between women with obesity in early pregnancy and those with a normal body mass index (BMI) in early pregnancy.MethodsThis was a retrospective cohort study of women with obesity in early pregnancy and those with a normal BMI who were seen at three teaching hospitals in South-East Nigeria. Statistical analysis was performed using Statistical Package for the Social Sciences version 17.0 software, with descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 9 publications
3
42
3
1
Order By: Relevance
“…This might be explained with the higher Cesarean Section rates in population of women with DM, bearing in mind that caesarean section excludes the creation of these injuries. Obesity and greater weight gain independently increase the risk of cesarean delivery, prolonged duration of labor, as well as of several adverse outcomes with vaginal delivery 4,5 , although our study could not confirm this statement. This is probably due to the fact that our study involved insufficient number of obese women with DM.…”
Section: Discussioncontrasting
confidence: 70%
“…This might be explained with the higher Cesarean Section rates in population of women with DM, bearing in mind that caesarean section excludes the creation of these injuries. Obesity and greater weight gain independently increase the risk of cesarean delivery, prolonged duration of labor, as well as of several adverse outcomes with vaginal delivery 4,5 , although our study could not confirm this statement. This is probably due to the fact that our study involved insufficient number of obese women with DM.…”
Section: Discussioncontrasting
confidence: 70%
“…A previous report stated that different determinant factors identified in the beginning of pregnancy, for example pre‐pregnancy weight related to insufficient and excessive GWG, can predict unfavorable gestational outcome . A retrospective cohort study also showed that a substantial proportion of normal weight women with excessive GWG have adverse outcomes . In contrast, inadequate weight gain is not associated with adverse outcome in obese women.…”
Section: Discussionmentioning
confidence: 99%
“…Iyoke et al . studying an African obstetric population found that early pregnancy obesity was associated with wide-ranging poor feto-maternal outcomes that increase the risk of pregnancy and childbirth-related morbi-mortality 16. WC, HC, and BMI (though not significant here despite the tendency; P = 0.092) were among the anthropometric variables found to diagnose obesity in pregnant Nigerians by Okereke et al 17.…”
Section: Discussionmentioning
confidence: 59%